2018
DOI: 10.1534/g3.118.200727
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Oxidative Stress Response Requires the NHR-49 Transcription Factor

Abstract: The overproduction of reactive oxygen species (ROS) in cells can lead to the development of diseases associated with aging. We have previously shown that C. elegans BRAP-2 (Brca1 associated binding protein 2) regulates phase II detoxification genes such as gst-4, by increasing SKN-1 activity. Previously, a transcription factor (TF) RNAi screen was conducted to identify potential activators that are required to induce gst-4 expression in brap-2(ok1492) mutants. The lipid metabolism regulator NHR-49/HNF4 was amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…It has been reported that NHR-49 activity positively regulates expression of detoxification genes such as glutathione-S-transferase (gst-4). While we were writing the manuscript another study indicated that flavin mono-oxygenase (fmo-2) upregulation during oxidative stress was dependent on NHR-49 (Qi et al, 2017;Goh et al, 2018;Hu et al, 2018). Our study shows that NHR-49 regulates detoxification enzymes in the context of infection as well.…”
Section: Nhr-49 Nuclear Hormone Receptor Regulates Both Metabolic Andmentioning
confidence: 64%
“…It has been reported that NHR-49 activity positively regulates expression of detoxification genes such as glutathione-S-transferase (gst-4). While we were writing the manuscript another study indicated that flavin mono-oxygenase (fmo-2) upregulation during oxidative stress was dependent on NHR-49 (Qi et al, 2017;Goh et al, 2018;Hu et al, 2018). Our study shows that NHR-49 regulates detoxification enzymes in the context of infection as well.…”
Section: Nhr-49 Nuclear Hormone Receptor Regulates Both Metabolic Andmentioning
confidence: 64%
“…It is important to note that ROS has also been linked to the death of the nematodes during E. faecalis infection ( 34 ). Additionally, NHR-49 is also activated during organic peroxide treatment and causes induction of cytoprotective factors, including FMO-2 ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that ROS has also been linked to the death of worms during E. faecalis infection(34). Additionally, NHR-49 is also activated during organic peroxide treatment and causes induction of cytoprotective factors including FMO-2(35,36).LD homeostasis entails a balance between lipid breakdown and synthesis. The homeostasis is maintained by conserved molecular players such as SREBP (SBP-1), PPARα (NHR-49), TOR, AMPK and hexosamine.…”
mentioning
confidence: 99%
“…NHR-49/PPAR-α is better known in C. elegans as a transcription factor that is important for the response to starvation (Van Gilst et al, 2005). However, recently NHR-49/PPAR-α was shown to mediate the defense response to exogenous oxidative stress (Goh et al, 2018;Hu et al, 2018). Thus, NHR-49/PPAR-α participates in host defense against biotic and abiotic stressors, and should be considered a key player in the organismal stress response alongside SKN-1/NRF, DAF-16/FOXO3, and HLH-30/TFEB (Blackwell et al, 2015;Lin et al, 2018;Tissenbaum, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified NHR-49, a nuclear receptor homologous to human PPAR-α and HNF4-α, as essential for fmo-2/FMO5 induction during exogenous oxidative stress (Goh et al, 2018;Hu et al, 2018). To examine the role of NHR-49/PPAR-α during infection, we checked fmo-2/FMO5 expression in nhr-49/PPARA null mutants (Liu et al, 1999;Van Gilst et al, 2005).…”
Section: Infection Induces Fmo-2/fmo5 Via Nhr-49/ppar-αmentioning
confidence: 99%